Facebook and Career Motivation - Dettwiler, Melissa; Gossett, Jessica; Pepper, Amy; Soderlund, Laura (My University, 2011)
While the use of the social network Facebook has continued to increase among college students (Nesbitt & Marriot, 2007), studies show that this group may not be aware of the influence their social networking profile content can have on potential employers (Peluchette & Karl, 2010). However, level of motivation with regard to finding a job has not been studied as it may relate to Facebook content choices among college students. This study found that Facebook users trust their privacy settings and feel that their profile content is a direct representation of themselves.
Color poster with text, images, and graphs.
Keywords: Facebook (Electronic resource); Job hunting--Computer network resources; College students--Social networks; Online social networks; Posters